An assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology : fiscal year 2011 (National Academies Press, 2011)
Since 1959, the National Research Council (NRC), at the request of the National Institute of Standards and Technology (NIST), has annually assembled panels of experts to assess the quality and effectiveness of the NIST measurements and standards laboratories. In 2011, the NRC evaluated three of the six NIST laboratories: the Center for Nanoscale Science and Technology (CNST), the NIST Center for Neutron Research (NCNR) and the Information Technology Laboratory (ITL). Each of these was addressed individually by a separate panel of experts; this report assesses CNST.